AB0075 Toll-like receptor 3 and interleukine 1b expression in circulating progenitor cells isolated from patients with rheumatoid arthritis. (23rd January 2014) - Lo Gullo, A.; Mandraffino, G.; Sardo, M. A.; Mamone, F.; Mandraffino, R.; Saitta, C.; Lo Gullo, R.; Versace, A. G.; Cinquegrani, M.; Saitta, A.
Abstract : Background: Circulating progenitor cells (CPCs), including CD34+ cells and endothelial progenitor cells (EPCs), play a role in delaying atherosclerosis and cardiovascular disease. Toll-like receptor 3 (TLR3), a member of the pathogen recognition receptors that mediates immune response and activates inflammatory genes, is involved in the development of atherosclerosis. TLR3 has been recently detected in EPCs and its "in vitro" activation appears to induce cytokine expression and apoptosis. We measured the expression of TLR3 and Interleukine1β- mRNA in CPCs isolated from patients with rheumatoid arthritis. Objectives: The aim was to evaluate whether systemic inflammation is associated with CPC number and CPC expression of TLR3 and IL-1β. Methods: CD34+ cells were isolated from peripheral blood from 21 patients with rheumatoid arthritis (RA patients) and from 21 matched controls. TLR3 and IL-1β -RNA expression were measured in enriched sample of CD34+ cells. Plasma C-reactive protein (CRP) and fibrinogen levels were also measured. Results: With respect to controls, CD34+ cell number was lower in RA patients. CRP and fibrinogen levels were higher in RA patients than in controls. TLR3-mRNA anf IL-1βexpression were significantly higher in RA patients with respect to controls. CRP and fibrinogen levels were associated with IL-1β e TLR3 expression; moreover, the increased expression of TLR3 and IL-1β were associated with lowering CPC number. Conclusions: RA is associated to an increased expression of TLR3 and of IL-1β in CPCs, which appear to affect the decrease of CPC number. It is likely that this novel association may at least in part contribute to explain the increase of cardiovascular morbidity and mortality in patients suffering from RA. Further studies could clarify whether the modulation of TLR3 expression in CPCs may modify the CV risk in patients affected by RA. References: Herbrig K et al. Endothelial dysfunction in patients with rheumatoid arthritis is associated with a reduced number and impaired function of endothelial progenitor cells. Ann Rheum Dis 2006;65(2):157-63. Yang M et al. The functional expression of TLR3 in EPCs impairs cell proliferation by induction of cell apoptosis and cell cycle progress inhibition. Int Immunopharmacol 2011, 11(12):2118-2124. Raicevic G et al. Inflammation modifies the pattern and the function of Toll-like receptors expressed by human mesenchymal stromal cells. Hum Immunol 2010, 71(3):235-244. Ito C et al. Cilostazol enhances IL-1beta-induced NO production and apoptosis in rat vascular smooth muscle via PKA-dependent pathway. Cell Signal 2002, 14(7):625-632. Zimmer S et al. Activation of endothelial toll-like receptor 3 impairs endothelial function. Circ Res 2011, 108(11):1358-1366. Disclosure of Interest: None Declared